Honos alit artes. Studi per il settantesimo compleanno di Mario Ascheri. I. La formazione del diritto comune Giuristi e diritti in Europa (secoli XII-XVIII) - Maffei, Paola; Varanini, Gian Maria (Reti Medievali E-Book, 2014)
The articles collected in the book offer insights on major aspects that determined the success and development of the "ius commune", progressively spread out across Europe, and from Europe to those parts of the world that felt the influence. Three prospects are hereby taken onto account, in a time span of seven centuries (XII-XVIII): the consilia of Jurists, the training paths in universities (texts, literary genres, doctrines, teaching and teachers) and the canonical science.